Ganoderma lucidum and Hypericum perforatum Exhibit Anti-Inflammatory, Antioxidant, and Anti-Androgen Effect in Rat Model of Experimental Polycystic Ovarian Syndrome - Okay, Gülin; Kırıcı, Pınar; Mavral, Nihal; Utkan Korun, Zeynep Ece; Annac, Ebru; Kaplan, Selçuk (Medical principles and practice, 2024)
Abstract Objective: Chronic inflammation is considered to be of key importance in the pathogenesis of polycystic ovarian syndrome (PCOS). Ganoderma lucidum polysaccharide (GLP) and Hypericum perforatum (HP) have been reported to have anti-inflammatory and antioxidant activities. We studied the effects of these agents on ovarian tissue in a rat model of experimental PCOS. Materials and Methods: Forty-two Sprague-Dawley female rats were divided into 6 groups with 7 animals in each group as listed below: Group 1: Control, Group 2: PCOS, Group 3: PCOS + HP, Group 4: HP only, Group 5: PCOS+ GLP, Group 6: GLP only. At the end of the experimental procedures, all the animals underwent bilateral oophorectomy and blood samples were collected. Ovarian tissue and blood samples were used for biochemical and histopathological analysis. Results: Follicle degeneration in the PCOS group showed a statistically significant increase compared to the other groups (p < 0.05). Cystic follicles were significantly reduced in the PCOS+GLP and PCOS+HP groups as compared to the PCOS group. Levels of tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) were elevated in PCOS rats (p < 0.01). Levels of sex hormone binding globulin (SHBG) levels were diminished (p < 0.01). Levels of malondialdehyde (MDA) and insulin-like growth factor 1 (IGF-1) were increased in PCOS rats as compared to the other groups (p < 0.02, p < 0.02, respectively). GLP supplementation diminished the levels of IGF-1 and MDA. GLP or HP supplementation increased reduced glutathione (GSH). Conclusion: GLP and HP treatment normalizes SHBG levels while correcting PCOS-induced hyperandrogenemia. Both herbs regulate the redox balance by decreasing the levels of MDA and increasing the level of GSH.